SHARIAH AND IMMUNITY CLAUSE IN 1999 CONSTITUTION OF THE FEDERAL REPUBLIC OF NIGERIA - Rabiu, S.O. (Jurnal Syariah, 2011)
Some people are always cover their abuse of office and hide it under the immunity clause, and thus is common in Nigeria. Their believe is that the immunity clause in 1999 Constitution of Federal Republic of Nigeria is license for them to embezzle and misappropriate public funds. On the contrary Islamic law does not distinguish between the rulers and the ruled in the application of law. The believe of the law is that the law which applies to the lead is equally applies to the leaders there is no distinction between the two of them. Although, this did not mean that Islamic law did not give respect to the leader, rather, the leader should respect the law of the land. The leader according to Islamic law should be honest, upright, trustworthy and show exemplary leadership in the society.